1999
DOI: 10.1021/ja990864o
|View full text |Cite
|
Sign up to set email alerts
|

Residue-Specific pKaMeasurements of the β-Peptide and Mechanism of pH-Induced Amyloid Formation

Abstract: The aggregation of the β-peptide into amyloid is a key pathological event in Alzheimer's disease. This process (β-amyloidosis) involves the conversion of soluble random coil, α-helical or β-sheet conformations into insoluble, aggregated β-pleated sheet structures. The pH is a significant extrinsic factor that influences β-amyloidosis, which must be related to the presence of ionizable groups in the β-peptide. To further evaluate this effect, we determined the dissociation constants (pK a) of the side chains fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
114
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(130 citation statements)
references
References 69 publications
16
114
0
Order By: Relevance
“…The shorter peptides show a lower degree or no cooperativity. The shortest fragment Ab (1)(2)(3)(4)(5)(6)(7)(8)(9) shows no cooperativity at all (r ¼ 1.00) in agreement with earlier observations that short segments do not exhibit cooperativity in the transition from PII to random coil [19].…”
Section: Cooperativity For Longer and Noncooperativity For Shorter Pesupporting
confidence: 91%
See 1 more Smart Citation
“…The shorter peptides show a lower degree or no cooperativity. The shortest fragment Ab (1)(2)(3)(4)(5)(6)(7)(8)(9) shows no cooperativity at all (r ¼ 1.00) in agreement with earlier observations that short segments do not exhibit cooperativity in the transition from PII to random coil [19].…”
Section: Cooperativity For Longer and Noncooperativity For Shorter Pesupporting
confidence: 91%
“…There is a small contribution of PII at 0°C. Trying to break the structural states down into three different peptide segments, (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17), (18)(19)(20)(21)(22)(23)(24), (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40), we arrive at a simplified model with overall characteristics as described in Fig. 6.…”
Section: Structural Transitions Of Alzheimer B-peptidementioning
confidence: 99%
“…The ␦-values of protons in Asp and Glu residues indicate that they are in the neutral, carboxylic acid form, whereas those in His, Lys, and Arg show they are charged. These charged states are consistent with the thorough study of A␤ pK a values reported previously (42). All of the resonances of A␤40 assigned here have been deposited in the BioMagResBank data base (www.bmrb.wisc.edu) under accession number 6257.…”
Section: Structural Characterization Of A␤40 By Nmr At Low Ph-supporting
confidence: 88%
“…These charges were then summed to calculate the total net charge on the peptide. The pK a values of Ma et al [20] measured for Ab in H 2 O gave very similar profiles of net charge vs. pH. The correlation of net charge with oligomerization was calculated using the paired Student t test implemented in Kaleidagraph 3.6 (Synergy Software).…”
Section: Calculation Of Net Charge Vs Phmentioning
confidence: 96%